2019
DOI: 10.3390/v11110991
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Analysis of Virioplankton from the Pelagic Zone of Lake Baikal

Abstract: This study describes two viral communities from the world’s oldest lake, Lake Baikal. For the analysis, we chose under-ice and late spring periods of the year as the most productive for Lake Baikal. These periods show the maximum seasonal biomass of phytoplankton and bacterioplankton, which are targets for viruses, including bacteriophages. At that time, the main group of viruses were tailed bacteriophages of the order Caudovirales that belong to the families Myoviridae, Siphoviridae and Podoviridae. Annotatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 59 publications
6
22
2
Order By: Relevance
“…Meanwhile, in Lake Baikal, recent studies have described a phage putatively infecting Polynucleobacter sp. [5], the virome associated with diseased sponges [25], and viromes from the epipelagic zone which suggested that the Baikal virome undergoes changes in composition across seasons [26].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, in Lake Baikal, recent studies have described a phage putatively infecting Polynucleobacter sp. [5], the virome associated with diseased sponges [25], and viromes from the epipelagic zone which suggested that the Baikal virome undergoes changes in composition across seasons [26].…”
Section: Introductionmentioning
confidence: 99%
“…Previous metagenomic studies of Lake Ontario and nearby Lake Erie found that Myoviridae were the dominant Caudovirales family (58). Likewise, metagenomic data from Lake Baikal showed a predominance of Myoviridae (59, 60), whereas Siphoviridae and Myoviridae relative abundances were similar in Lakes Michigan, Pavin, and Bourget (61, 62). Therefore, our findings of highly abundant Siphoviridae relative to Myoviridae in Hamilton Harbour contrasts previous studies of Caudovirales communities in other freshwater lakes.…”
Section: Discussionmentioning
confidence: 96%
“…K-strategists among macro-organisms can be more competitive and better adapted to emerging micro-environmental characteristics [85]. We hypothesise that, in the circumstances of a scarce reserve of nutrients in the oligotrophic Lake Baikal ecosystem [7,9], the K-strategy chosen by PaBG allows it to exploit the available resources more efficiently. Moreover, based on this thinking, we could expect to find K-strategist jumbo-phages in diverse, balanced, complex, competitive multispecies communities.…”
Section: Discussionmentioning
confidence: 99%
“…Baikal is the deepest ancient lake in the world, and its autochthonous organic matter has been the subject of numerous studies [6,7]. In particular, a high diversity of bacteriophages in the water of Baikal has been reported [8,9]. PaBG infects Pseudomonas aeruginosa, a common inhabitant of freshwater [10].…”
Section: Introductionmentioning
confidence: 99%